Two new species of shovel-jaw carp Onychostoma (Teleostei: Cyprinidae) from southern Vietnam - Hoang, Huy Duc; Pham, Hung Manh; Tran, Ngan Trong (Zootaxa, 2015)
Two new species of large shovel-jaw carps in the genus Onychostoma are described from the upper Krong No and middle Dong Nai drainages of the Langbiang Plateau in southern Vietnam. These new species are known from streams in montane mixed pine and evergreen forests between 140 and 1112 m. Their populations are isolated in the headwaters of the upper Sre Pok River of the Mekong basin and in the middle of the Dong Nai basin. Both species are differentiated from their congeners by a combination of the following characters: transverse mouth opening width greater than head width, 14−17 predorsal scales, caudal-peduncle length 3.9−4.2 times in SL, no barbels in adults and juveniles, a strong serrated last simple ray of the dorsal fin, and small eye diameter (20.3−21.5% HL). Onychostoma krongnoensis sp. nov. is differentiated from Onychostoma dongnaiensis sp. nov. by body depth (4.0 vs. 3.2 times in SL), predorsal scale number (14−17 vs. 14−15), dorsal-fin length (4.5 vs. 4.2 times in SL), caudal-peduncle length (3.9 vs. 4.2 times in SL), colour in life (dark vs. bright), and by mitochondrial DNA (0.2% sequence divergence). Molecular evidence indicates that both species are members of Onychostoma and are distinct from all congeners sampled (uncorrected sequence divergences at the 16S rRNA gene of >2.0% for all Onychostoma for which homologous 16S rRNA sequences are available).